2018
DOI: 10.37358/rc.18.3.6182
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical, Imagistic and Structural Study of Pharamagnetic Substances in Cervical Tumors

Abstract: Along with the findings of recent years in medical imaging, a wide range of contrast agents have been developed and used in order to improve the quality of the images acquired and to get a diagnosis with the highest accuracy. Modern substances used in nuclear magnetic resonance imaging contain ions with one or more free electrons, which have fewer side effects and are eliminated by the kidney in a short time. This is used in MRI practice in T1 section, where these substances reduce relaxation time and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The value of this protein's expression has a normal limit in the free mucosa, being somewhat higher in adenomas, and the maxima in adenocarcinomas [19][20][21]. Researchers found a correlation between the histological degree of malignancy and the depth of tumor infiltration in the wall [22].…”
Section: Resultsmentioning
confidence: 99%
“…The value of this protein's expression has a normal limit in the free mucosa, being somewhat higher in adenomas, and the maxima in adenocarcinomas [19][20][21]. Researchers found a correlation between the histological degree of malignancy and the depth of tumor infiltration in the wall [22].…”
Section: Resultsmentioning
confidence: 99%
“…Besides video-assisted thoracoscopy, a number of noninvasive interdisciplinary approaches can be used, which, according to the literature, have shown that they can improve the parameters mentioned above [8,9].…”
mentioning
confidence: 99%
“…The characteristic of ovarian tumors is underlined by the following findings: it shows a high degree of macroscopic polymorphism, starting from the periphery towards the center of the tumor and microscopically, sometimes in the same section encountering a multitude of aspects [4][5][6]. The incidence of the disease is increasing, the history and clinical aspects are nonspecific, and the varied nature of the patients, early diagnosis is difficult or even impossible to consider [7][8][9].…”
mentioning
confidence: 99%